THE ISSUES OF THE CONCEPT AND CRIMINAL LIABILITY OF THE ORGANIZER OF THE CRIME - Poghosyan, Sevak (State and Law, 2021)
The article discusses the functions of a crime organizer, the nature and content of the actions taken. The author concludes that the separation of the organizer’s institute is not expedient. The organizer either performs the functions of an instigator or a facilitator or combines them. Therefore, in cases where a person carries out the actions of an instigator and a facilitator, when qualifying his action, in addition to reference to Article 38, reference should also be made to part 4 and 5 of that Article. If it unites two or more persons, then, when caught at that moment, the act should be described as a preparation for a deliberate crime, however, when caught during or after the crime, it should be described as an incitement. The mentioned innovations, in the author’s opinion, can contribute to the improvement of criminal law theory and practice.